2010
DOI: 10.1016/j.jsps.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the rate of therapeutic adherence among outpatients with T2DM in Egypt

Abstract: An improvement with the adherence to oral hypoglycemic agent(s) may be achieved through continuing patient education about diabetes, improvement of patients' economical levels as well as a reduction in the cost of medication. Pharmaceutical companies have to be involved and pharmacists have to be payed for helping chronically ill patients to take their medicines correctly for improving clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
61
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 36 publications
13
61
3
3
Order By: Relevance
“…The difference in the level of compliance was statistically significant (p=0.001). Similar observation was made in one of the previous study [17]. However, other studies have not found any positive correlation between family status and compliance [5,18].…”
Section: Discussionsupporting
confidence: 90%
“…The difference in the level of compliance was statistically significant (p=0.001). Similar observation was made in one of the previous study [17]. However, other studies have not found any positive correlation between family status and compliance [5,18].…”
Section: Discussionsupporting
confidence: 90%
“…This study explored therapeutic adherence and the factors contributing to the adherence of diabetic patients in Jazan region. Non adherence with medication in this study was similar to the earlier finding in Egypt [7], Palestine [10], France [4], Poland [14] and Saudi Arabia [11] In Palestine study, non-compliance was divided into two categories ( 51.4 % poor compliance and 6.5 % noncompliance ) [10]. In France the non-compliance was divided into two categories also (49% medium adherence and 12% poor adherence ) [4].…”
Section: Discussion:-supporting
confidence: 88%
“…Female patients were found by some researchers to have better adherence [15] while some studies suggested otherwise [16]. In addition, some studies could not find a relationship between gender and adherence to medication, this difference may be due to geographical variation in their education, and social factors [7].…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…(7,8) To date, most of the studies conducted to evaluate AED adherence among PWE did not account for the influence of a wide range of variables (e.g. demographic, disease and treatment patterns).…”
Section: Introductionmentioning
confidence: 99%